2002
DOI: 10.1111/j.1748-7692.2002.tb01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Evidence of Thermal Stress From Overheating in Uk Breeding Gray Seals

Abstract: Gray seals (Halichoerus grypus) in the UK exhibit clear preferences for pupping close to pools of water on inland breeding sites. The reasons for this are unclear as seals are thought to derive all their water requirements from the metabolism of fat. Likewise, the prospect of seals overheating during the UK's cool, damp, autumnal breeding seasons, has seemed unlikely, but has not been previously explored. Here, we provide preliminary behavioral evidence of thermal stress in female gray seals breeding on the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 31 publications
3
36
1
Order By: Relevance
“…The strong impacts of solar radiation on T S are consistent with previous suggestions outlining the importance of this variable in affecting thermoregulatory behavior in pinnipeds (Beentjes, 2006;Twiss et al, 2002;Campagna and Le Boeuf, 1988;White and Odell, 1971). Direct exposure to solar radiation results in not only the animal absorbing heat but also the warming of the surrounding substrate, lowering any heat gradient and possibly adding to the heat gain of an animal through conduction (Campagna and Le Boeuf, 1988).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The strong impacts of solar radiation on T S are consistent with previous suggestions outlining the importance of this variable in affecting thermoregulatory behavior in pinnipeds (Beentjes, 2006;Twiss et al, 2002;Campagna and Le Boeuf, 1988;White and Odell, 1971). Direct exposure to solar radiation results in not only the animal absorbing heat but also the warming of the surrounding substrate, lowering any heat gradient and possibly adding to the heat gain of an animal through conduction (Campagna and Le Boeuf, 1988).…”
Section: Discussionsupporting
confidence: 89%
“…Physiological or behavioral thermoregulation mechanisms often drive reproductive behavior in pinnipeds. Female New Zealand fur seals, southern sea lions, Juan Fernandez fur seals and grey seals are known to migrate to tide pools, the shoreline or directly into the ocean during periods of increased solar radiation and air temperature (Twiss et al, 2002;Francis and Boness, 1991;Campagna and Le Boeuf, 1988). Males defending territories with access to water, in which greater numbers of females aggregate, enjoy increased copulatory success compared with that of males guarding waterless areas (Francis and Boness, 1991;Campagna and Le Boeuf, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavioral thermoregulatory mechanism, described for the first time in a tropical pinniped in the present paper, the GSL, is shared by other temperate pinnipeds. Southern sea lions Otaria flavescens, Juan Fernandez fur seals Arctocephalus philippii, and grey seals also use behavioral thermo regulatory mechanisms, demonstrating movements towards shorelines and into the ocean in summers, when temperatures are high (Campagna & Le Boeuf 1988, Francis & Boness 1991, Twiss et al 2002. Our results are in agreement with Wolf et al (2005), who suggested that GSL habitat preferences are linked to thermoregulatory requirements.…”
Section: Changes In Terrestrial Microhabitat Preferencessupporting
confidence: 90%
“…Thus, the thermoregulation response is especially challenging for pinnipeds due to the differences in thermal fluxes in both environments and also because their large body size limits the effectiveness of surface heat loss (Norris et al 2010). Behavioral responses such as the thermoregulation mechanism are known to be important drivers of haul-out patterns in many temperate pinniped species (White & Odell 1971, Witthow et al 1971, Odell 1974, Campagna & Le Boeuf 1988, Francis & Boness 1991, Twiss et al 2002. However, little is known about temporal variations in haul-out behavior and thermoregulation of pinnipeds inhabiting low latitudes.…”
Section: Introductionmentioning
confidence: 99%